The Trump Administration and Japan: Challenges and Visions for Japan's Foreign and Security Policy in the New Era. (2nd January 2017) - Unknown
Abstract : It is possible that Donald Trump's success in the US presidential election of November 2016 will touch off the greatest transformation in world politics since World War Two. This is because, for the first time, the presidency of the United States—a country that since World War Two has consistently upheld the liberal world order—has been won by a man who asserts that the US national interests will take precedence over international cooperation. If so, Japan could be one of the most profoundly affected countries. Japan has thus far accepted its status as a junior partner within the US security framework and—without any significant military power of its own—has devoted itself to economic development. Although it is difficult to predict what Mr. Trump's policies will be, there is a possibility, based on the statements he has made to date, that he will be calling for Japan to become more self-reliant. Although his comprehension of the Japan-US security arrangements is fraught with misconceptions, there is ample possibility that he will ultimately opt to maintain the current Japan-US security framework. However, given that the average defense expenditure of NATO countries is 2% of their GDPs, and that the average expenditure of OECD countries on official development assistance (ODA) is 0.7% of their GDPs, it is highly questionable whether Mr. Trump will approve of Japan's level of defense spending (less than 1% of its GDP) or of its level of spending on ODA (approximately 0.2% of its GDP). It would not be such a bad thing for Japan to become more self-reliant in terms of security. It is almost unnatural for Japan to maintain this relationship as it is, in the form that it has taken since before Japan's postwar reconstruction. However, in the context of international relations in East Asia, it has long been taken for granted that this is Japan's basic stance. Changing this will be no easy task—either domestically or in terms of Japan's relations with neighboring countries. In these respects, the authors of this paper decided to consider the question of how Japan should develop its foreign and security policy, and to offer some proposals in this regard.